Poison and Proof: Forensic Toxicology and the Science of Drug-Facilitated Crime - Anurag Gupta (AG Volumes, 2026)
Drug-facilated crimes, such as drug-facilated sexual assault (DFSA), pose a serious problem for forensic science and the criminal justice system because incapacitating agents can have a short half-life and numerous pharmacological effects. The review considers the contribution of forensic toxicology to the detection, identification and interpretation of the toxic components of DFCs. It addresses the pharmacological properties of potentially involved substances such as alcohol, benzodiazepines, γ-hydroxybutyrate (GHB), ketamine, opioids, cannabinoids, stimulants, antihistamines and novel psychoactive substances (NPS). The review also discusses the collection and storage methods for biological specimens, current analytical methods including GC–MS, LC–MS/MS and HRMS, toxicokinetics, detection wind006Fws, and polydrug exposure. Further, it identifies forensic, legal, and ethical issues in the Indian scenario, presents new technologies such as ‘AI’, ‘Metabolomics', and advanced analytical platforms that are likely to further bolster the science of toxicological work and enhance the scientific integrity of the toxicological evidence.